2018
DOI: 10.21873/anticanres.12375
|View full text |Cite
|
Sign up to set email alerts
|

COX2/PTGS2 Expression Is Predictive of Response to Neoadjuvant Celecoxib in HER2-negative Breast Cancer Patients

Abstract: COX2 overexpression is predictive of pCR in patients with celecoxib-treated tumors. The efficacy of celecoxib in breast cancer might be improved by quantification of COX2 gene expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…Cyclooxygenase-2 (COX-2), the enzyme that catalyzes prostaglandin synthesis, has been extensively investigated as a target in cancer therapy and prevention ( Wang et al, 2005 ; Zha et al, 2001 ; Gupta et al, 2000 ; Yoshimura et al, 2000 ; Krishnan & Feldman, 2010 ; Sun et al, 2018 ). COX-2 is overexpressed in putative cancer precursor inflammatory lesions in tissues such as breast and prostate, in a variety of cancer cell lines, as well as in macrophages and other cells in the tumor microenvironment ( de Cremoux et al, 2018 ; Sano et al, 2018 ). Calcitriol regulates the expression of several genes in the prostaglandin pathway; in vitro and in vivo studies demonstrate that calcitriol + nonsteroidal anti-inflammatory agents which inhibit COX-2 potentiate the growth inhibitory effects of calcitriol ( Davila-Gonzalez et al, 2017 ; Basudhar et al, 2017 ).…”
Section: Anticancer Effects Of Vitamin D Compoundsmentioning
confidence: 99%
“…Cyclooxygenase-2 (COX-2), the enzyme that catalyzes prostaglandin synthesis, has been extensively investigated as a target in cancer therapy and prevention ( Wang et al, 2005 ; Zha et al, 2001 ; Gupta et al, 2000 ; Yoshimura et al, 2000 ; Krishnan & Feldman, 2010 ; Sun et al, 2018 ). COX-2 is overexpressed in putative cancer precursor inflammatory lesions in tissues such as breast and prostate, in a variety of cancer cell lines, as well as in macrophages and other cells in the tumor microenvironment ( de Cremoux et al, 2018 ; Sano et al, 2018 ). Calcitriol regulates the expression of several genes in the prostaglandin pathway; in vitro and in vivo studies demonstrate that calcitriol + nonsteroidal anti-inflammatory agents which inhibit COX-2 potentiate the growth inhibitory effects of calcitriol ( Davila-Gonzalez et al, 2017 ; Basudhar et al, 2017 ).…”
Section: Anticancer Effects Of Vitamin D Compoundsmentioning
confidence: 99%
“…COX2 produces prostaglandin-endoperoxide synthase (PTGS) under the regulation of specific stimulus events, such as responding to physiological stress responses, infection, and inflammation. Usually, COX2 and PTGS2 are combined to represent [ 65 , 66 , 67 , 68 ]. In this study, after conducting network-feature topology analysis on the PR candidate compounds–depression targets network, it was found that COX2 and PTGS2 have the same degree value, which is the largest value among the targets.…”
Section: Discussionmentioning
confidence: 99%
“…Combination of celecoxib with other chemotherapies including taxanes have been tested in preclinical models and clinical trials and showed some indication of efficacy ( 73 , 74 ). However, these trials revealed an unmet need for biomarkers to better identify which cancers may respond to combination treatments that include celecoxib ( 75 , 76 ). While downregulation of E-cadherin may not always be necessary for response to celecoxib, our study shows that COX-2 can maintain cell-to-cell adhesions in HR – aggressive BC cells through GSK3β inhibition.…”
Section: Discussionmentioning
confidence: 99%